Perancangan dan Pembuatan Aplikasi Visualisasi 3D Interaktif Masjid Agung Jawa Tengah Menggunakan Unity3D - Irham Fa'idh Faiztyan; R. Rizal Isnanto; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2015)
Previously, people who want to visit a tourist attraction should come to that place. If you can’t visit it normally, you can only read or heard from a source. Therefore made 3-dimensional visualization application. The object to be visualized in this research is Great Mosque of Central Java. This application aims to facilitate the introduction of the Great Mosque of Central Java. This application is created using Unity3D and Sketchup software, where the programming language used is UnityScript and JavaScript. The design phase made using Multimedia Development Life Cycle, and then proceed with the design using Flowchart. Implementation phase is done by implementing a 3D model and program implementation. The testing phase is done with a black-box method, as well as testing of the frame rate per second, memory and processor usage, how long rendering process, and user testing. The results show that this application runs well on Windows operating systems. Buttons and functions within the application has been running well with the respective functionality. From the test results on the application of the Great Mosque of Central Java visualization can be shown that the process of rendering both real time and non real time rendering requires a high performance from graphics card and processor. Based on the testing that has been done, the application is quite easy to run by the user, the objects that exist in the application is quite similar to the original object, and this application provides benefits to its users.